Resiliencia De Los Estudiantes De Enfermería Durante La Pandemia Del Covid-19. Revisión Narrativa De La Literatura (2022)
Title: Resilience of nursing students during the covid-19 pandemic. Revision Literature narrative Introduction: Coronavirus infection has increased worldwide With the passing of time, last March 2020 (WHO) declared it a global pandemic, bringing as consequence problems in the physical and mental health of the population. For this study the target population They were university students, specifically undergraduate nursing. The purpose of this study is: Describe the resilience of nursing students during the COVID-19 pandemic, through based on scientific evidence.